Risperidone oral disintegrating mini-tablets: A robust-product for pediatrics - El-Say Khalid M.; Ahmed Tarek A.; Abdelbary Maged F.; Ali Bahaa E.; Aljaeid Bader M.; Zidan Ahmed S. (Acta Pharmaceutica)
This study was aimed at developing risperidone oral disintegrating mini-tablets (OD-mini-tablets) as age-appropriate formulations and to assess their suitability for infants and pediatric use. An experimental Box-Behnken design was applied to assure high quality of the OD-mini-tablets and reduce product variability. The design was employed to understand the influence of the critical excipient combinations on the production of OD-mini-tablets and thus guarantee the feasibility of obtaining products with dosage form uniformity. The variables selected were mannitol percent in Avicel (X1), swelling pressure of the superdisintegrant (X2), and the surface area of Aerosil as a glidant (X3). Risperidone-excipient compatibilities were investigated using FTIR and the spectra did not display any interaction. Fifteen formulations were prepared and evaluated for preand post-compression characteristics. The prepared ODmini- tablet batches were also assessed for disintegration in simulated salivary fluid (SSF, pH 6.2) and in reconstituted skimmed milk. The optimized formula fulfilled the requirements for crushing strength of 5 kN with minimal friability, disintegration times of 8.4 and 53.7 s in SSF and skimmed milk, respectively. This study therefore proposes the risperidone OD-mini-tablet formula having robust mechanical properties, uniform and precise dosing of medication with short disintegration time suitable for pediatric use.